I'm afraid I don't see the models you have written about although I do know the answer. (C= Courtney's age, S= Shilo's age)
Shilo is 7 years older then Courtney, which equals to C+7=S.
While at the same time Shilo is 13 years younger then twice Courtney's age. This turns into Cx2-13=S.
c+7=cx2-13. This is the equation, now lets work it out.
Add 13 on each side and you get
c+20=2c
Now we subtract c from each side and we get
20=c Therefor we have found out that Courtney is 20 years old.
Shilo being 7 years older then Courtney is 27
Answer:
7
Step-by-step explanation:
By Basic proportionality theorem:
![\frac{10}{8} = \frac{3x - 6}{12} \\ \\ \frac{10 \times 12}{8} = 3x - 6 \\ \\ \frac{120}{8} = 3x - 6 \\ \\ 15 = 3x - 6 \\ 15 + 6 = 3x \\ 21 = 3x \\ \frac{21}{3} = x \\ 7 = x \\ \\ \huge \red { \boxed{x = 7}}](https://tex.z-dn.net/?f=%20%5Cfrac%7B10%7D%7B8%7D%20%20%3D%20%20%5Cfrac%7B3x%20-%206%7D%7B12%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Cfrac%7B10%20%5Ctimes%2012%7D%7B8%7D%20%20%3D%203x%20-%206%20%5C%5C%20%20%5C%5C%20%20%5Cfrac%7B120%7D%7B8%7D%20%20%3D%203x%20-%206%20%5C%5C%20%20%5C%5C%2015%20%3D%203x%20-%206%20%5C%5C%2015%20%2B%206%20%3D%203x%20%5C%5C%2021%20%3D%203x%20%5C%5C%20%20%5Cfrac%7B21%7D%7B3%7D%20%20%3D%20x%20%5C%5C%207%20%3D%20x%20%5C%5C%20%20%5C%5C%20%20%5Chuge%20%5Cred%20%7B%20%5Cboxed%7Bx%20%3D%207%7D%7D)
Answer:
Ooof
Step-by-step explanation:
Answer:
2/5
Step-by-step explanation:
Ok there are 4+3+1+2 pairs of socks in all... Aka 10 sock pairs in all.
There are 4 white pairs. So the probability she selects a white pair is 4/10.
4/10 can be reduced to 2/5.
Answer:
Step-by-step explanation:Given that the numerator of a given fraction is 4 less than its denominator.
Also given that 3 is subtracted from the numerator and 5 is added to the denominator, the fraction becomes one by fourth .
Let the fraction be
Since the numerator of a given fraction is 4 less than its denominator we have,
Numerator=Denominator-4
⇒ a=b-4
Since 3 is subtracted from the numerator and 5 is added to the denominator, the fraction becomes one by fourth we have
4(a-3)=1(b+5)
4a-12=b+5
4a-b=17
4(b-4)-b=17 ( ∵ a=b-4)
4b-16-b=17
3b=17+16
3b=33
⇒ b=11
Now put b=11 in a=b-4 we get
a=11-4
⇒ the fraction is a/b=7/11